Me diga o que bebes e te direi que homem és: representações masculinas nos anúncios de whisky - Pichinin , Thais Ortega (2024)
Although men are portrayed in countless beverage advertisements, historically they have not always been represented in the same way. Just as the changes in female representations in advertisements have been and still are widely discussed, this work aims to observe these changes in relation to male representations, a less debated subject. The feminist empowerment movements have brought several changes in female representations in advertisements, and in how brands viewed these bodies, but these movements also brought changes in the understanding of the symbolic values related to male representations, which is why this work aims to understand how male characters are represented in whiskey advertisements, and thus map the symbolic values that are being triggered by these representations, and analyze which discourses are present and by which voices. For this we will use Discourse Analysis, the Bakhtin Circle and Intericonicity as methodology. The corpus will comprise whisky advertisements broadcast on Instagram between 2021 and 2023, from Johnnie Walker, Singleton, Jack Daniel’s and Chivas brands. As a main result, we can highlight that we are going through a process of transformation of representations, but even though these are reconstructed, they often return to old discourses, the “already said”, that is, some values are still maintained.